2004
DOI: 10.1111/j.1365-2362.2004.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, age and seasonal effects on IgA deficiency: a study of 7293 Caucasians

Abstract: The prevalence of SIgAD and subnormal SIgA levels is increased in males. There exists a significant influence of gender, age and seasons on SIgA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 27 publications
7
61
0
Order By: Relevance
“…Secretory IgA-deficient individuals have low levels of serum IgA and of mucosal IgA. The percent of the world's human population deficient in IgA ranges from 0.001 to 0.1% (245). In IgA-deficient individuals, the decrease of sIgA is compensated by increased IgM and IgG levels (75).…”
Section: Iga Deficiencymentioning
confidence: 99%
“…Secretory IgA-deficient individuals have low levels of serum IgA and of mucosal IgA. The percent of the world's human population deficient in IgA ranges from 0.001 to 0.1% (245). In IgA-deficient individuals, the decrease of sIgA is compensated by increased IgM and IgG levels (75).…”
Section: Iga Deficiencymentioning
confidence: 99%
“…The prevalence in samples submitted to hospital laboratories is generally higher than in the population as a whole. 37,38 The prevalence varies in di¡erent racial groups in the same geographical area. Among healthy blood donors, the prevalence ranges from one in 328--633 for those of European ancestry 39--41 to one in 5000 in China and one in 18,500 in Japan 42 and is even lower in India.…”
Section: Prevalence Of Primary Immunoglobulin a Deficiencymentioning
confidence: 99%
“…A study in 7,293 Caucasians showed that serum immunoglobulin A (IgA) levels are highest in winter. The surfaces of the gastrointestinal, respiratory, and genitourinary tracts represent major sites of potential attack by invading micro-organisms and IgA, as the principal antibody class in the secretions that bathe these mucosal surfaces, is an important first line of defense against infection [39]. Yet, while infection-related mortality was not found to be higher in the winter months, it is possible that infections contributed to CVD mortality [40].…”
Section: Seasonal Patternsmentioning
confidence: 82%